Analysis of Islamic Human Development Index Maqashid Syariah Perspective - Edi Purwanto; Miyasto Miyasto; Mardani Mardani (BPJP - STEI, 2021)
This research is based on the benchmark Human Development Index (HDI) is not comprehensive and has not been by Maqashid al Syariah. This research aims to find out the Islamic Human Development Index (Islamic HDI) based on the perspective of Maqashid al Syariah, along with its dimensions and indicators. The research method used is the study of literature in-depth, by comparing some literature related to research themes. Theories used include Maqashid al Syariah and Human Development Index. The results showed the Islamic HDI consisted of five-dimensional indices, namely Faith (ad-din), Life (an-nafs), Intellect (al-aql), Offspring (an-nasl), and Wealth (al-mal). As for indicators per dimension, among others, the Faith Dimension consists of two indicators, namely obedience, and integrity. The dimensions of the Life include life expectancy and multidimensional poverty. The dimensions of Intellect include the level of education and literacy. The Offspring Dimension consists of birth rate indicators and infant mortality rates, and the Wealth Dimension includes purchasing power ability (per capita income indicator) and Gini ratio indicator.